Tunable Plasmonic Wavelength Demultiplexing Device Using Coupled Resonator System - Xiao-Meng Geng; Tie-Jun Wang; Da-Quan Yang; Lin-Yan He; Chuan Wang (IEEE Photonics Journal, 2016)
Plasmonic devices have recently been widely studied recently due to their properties of light confinement, which shows great potential applications in optical information processing. Here, in exploiting plasmonic metal–insulator–metal (MIM) side-coupled cavities, we present a theoretical implementation of the plasmonic wavelength demultiplexer (PWDM) device. The proposed PWDM device is designed using an add–drop-drop structure, which consists of one input port and two output ports. The transmission of the plasmonic field on the drop ports could be tuned by changing the gap between the waveguide and plasmonic resonators. Our approach captures the wavelength demultiplexing properties of the plasmonic field using the proposed structure. The performance of our device is analyzed based on the structure with three waveguides coupled with two square cavities.